A second documented record of Spectacled Petrel Procellaria conspicillata in Argentine waters - Seco Pon, Juan Pablo; William III, Stein
The Spectacled Petrel Procellaria conspicillata is endemic to Inaccessible Island, in the Tristan da Cunha group (central South Atlantic). The species is considered an occasional visitor to Argentina and there are few records of the species in national waters. On 13 February 2014, two birds were observed (and photographed) 89 nautical miles southeast off Buenos Aires Province at 38°55'S, 56°00'W. This record represents the second documented record of Spectacled Petrel for Argentina. Fil: Seco Pon, Juan Pablo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencia Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: William III, Stein. Pontchartrain Institute For Environmental Sciences; Estados Unidos